Integrated Marketing Communication Strategy in Creating Brand Equity of Sultan Agung Islamic Hospital as Sharia Hospital - Nabila Ikrima (Future Science)
Brand equity needs to be built by the organization so that the produced products whether goods or services can be easily recognized and remembered by the consumers. Sultan Agung Islamic Hospital as a health service provider also needs to build brand equity through Integrated Marketing Communication Strategy so that the predicate as the Sharia Hospital will be better known by consumers. The objective of this research is to know the strategy applied by Sultan Agung Islamic Hospital in creating brand equity as the sharia hospital. This research is qualitative descriptive research that aims to explain the implementation of marketing communication strategy in Sultan Agung Islamic Hospital using the purposive sampling technique. The research informant consisted of Hospital representatives consisting of four people, they are The Director of Sultan Agung Islamic Hospital, the Public Relations and Marketing Manager, Public Relations Staff, and Marketing Staff. The data was obtained through in-depth interviews and observation. The result shows that Sultan Agung Islamic Hospital has implemented an integrated marketing communication strategy through advertising activity, public relations, sponsorship, sales promotion, and on-site communication. All Integrated Marketing Communication activities and programs are conducted to strengthen the predicate of Sultan Agung Islamic Hospital as a sharia hospital.